2014
DOI: 10.1521/jscp.2014.33.4.295
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Priming Attachment Styles on Excessive Reassurance Seeking and Negative Feedback Seeking in Depression

Abstract: Two studies examined the associations among attachment styles, excessive reassurance seeking (ErS) and negative feedback seeking (NFS) in depression. in Study 1 (n = 303), undergraduate students completed measures assessing attachment style, depressive symptoms, and ErS following either an imaginary interpersonal (friend and partner) or achievement prime. in Study 2 (n = 202), undergraduates completed the same measures in addition to completing an index of NFS following an imaginary interpersonal (partner) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Individuals who are anxiously attached or high in sociotropy may excessively seek reassurance from their relationship partners in an attempt to quell their doubt and fulfil their need for acceptance and comfort. Several studies have, in fact, demonstrated that anxious attachment is significantly associated with higher overall and daily levels of excessive reassurance seeking (Abela et al., ; Davila, ; Evraire & Dozois, ; Evraire, Ludmer, & Dozois, ; Shaver, Schachner, & Mikulincer, ). Moreover, the abandonment component of anxious attachment (Davila, ) and core beliefs surrounding abandonment (Evraire & Dozois, ) appear to be most strongly associated with excessive reassurance seeking.…”
Section: Interpersonal Vulnerability To Depression and Stress Generationmentioning
confidence: 99%
“…Individuals who are anxiously attached or high in sociotropy may excessively seek reassurance from their relationship partners in an attempt to quell their doubt and fulfil their need for acceptance and comfort. Several studies have, in fact, demonstrated that anxious attachment is significantly associated with higher overall and daily levels of excessive reassurance seeking (Abela et al., ; Davila, ; Evraire & Dozois, ; Evraire, Ludmer, & Dozois, ; Shaver, Schachner, & Mikulincer, ). Moreover, the abandonment component of anxious attachment (Davila, ) and core beliefs surrounding abandonment (Evraire & Dozois, ) appear to be most strongly associated with excessive reassurance seeking.…”
Section: Interpersonal Vulnerability To Depression and Stress Generationmentioning
confidence: 99%
“…As a proactive behavior, feedback seeking is the behavior of individuals who involves actively seeking valuable information in the organization so that it can be adapted to the organization’s and individuals’ development requirement 13. A supportive coworker feedback environment encourages coworkers to seek feedback,14 thereby enabling employees to improve their creativity 10.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some research suggests that reassurance seeking is the manifestation of an anxious attachment that results in a propensity for excessively seeking reassurance from others to combat their fears of rejection and abandonment. 20 A number of studies have supported an association between reassurance seeking and increased attachment anxiety. 2021 Less is known about reassurance seeking among those who are socially avoidant.…”
Section: Introductionmentioning
confidence: 99%
“…20 A number of studies have supported an association between reassurance seeking and increased attachment anxiety. 2021 Less is known about reassurance seeking among those who are socially avoidant. However, previous studies have found that social anxiety 22 and shyness 23 are associated with reassurance seeking.…”
Section: Introductionmentioning
confidence: 99%